2019
DOI: 10.1093/ajcn/nqy262
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolites predict both insulin resistance and incident type 2 diabetes: a metabolomics approach within the Prevención con Dieta Mediterránea (PREDIMED) study

Abstract: Background Insulin resistance is a complex metabolic disorder and is often associated with type 2 diabetes (T2D). Objectives The aim of this study was to test whether baseline metabolites can additionally improve the prediction of insulin resistance beyond classical risk factors. Furthermore, we examined whether a multimetabolite model predicting insulin resistance in nondiabetics can also predict incident T2D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…A recent report of the PREDIMED Trial study indicates a non-targeted metabolomics approach. This investigation found that plasma metabolites predict insulin resistance and incident T2DM 26 . Metabolite profile of individuals with normal fasting glucose is also available in this report.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A recent report of the PREDIMED Trial study indicates a non-targeted metabolomics approach. This investigation found that plasma metabolites predict insulin resistance and incident T2DM 26 . Metabolite profile of individuals with normal fasting glucose is also available in this report.…”
Section: Discussionmentioning
confidence: 79%
“…A large number of metabolomics studies have been conducted in patients with T2DM [24][25][26][27][28] . Metabolomics analysis has, however, not been widely used to identify altered metabolism in healthy people who are at risk for T2DM 6,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several metabolomic techniques were applied to the identification of metabolic signatures associated with T2DM [10,11,12,13,14,15,16,17]. Data in this research field were extensive, revealing new diagnostic/prognostic disease biomarkers [14], or metabolic markers of response to targeted therapies [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of sphingomyelins have been shown to play a critical role in cardiovascular dysfunction including insulin resistance, atherosclerosis, and cardiomyopathy [36]. While levels of SM C16:0 were not shown to be associated with the clinical features of MetS in a young Japanese sample [37], SM C16:0 was shown to be associated with insulin resistance in a Southern European cohort at high risk for cardiovascular disease [38]. Sphingomyelins likely play a significant role in chronic inflammation and may therefore be implicated in multiple metabolic diseases, including those of old age such as dementia [34,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%